Understanding Visual Novel As Artwork of Visual Communication Design - Dendi Pratama; Winny Gunarti; Taufiq Akbar (Institut Seni Indonesia Denpasar, 2017)
Visual Novel is a kind of audiovisual game that offers visual strength through the narrative and visual characters. The developer community of Visual Novel (VN) Project Indonesia indicated a limited local game developer that produces Visual Novel of Indonesia. In addition, Indonesian Visual Novel production was also more influenced by the style of anime or manga from Japan. Actually, Visual Novel is part of the potential of creative industries products. The study is to formulate the problem, how to understand Visual Novel as artwork of visual communication design, especially among students? This research is a case study conducted on visual communication design student at the University Indraprasta PGRI Jakarta. The results showed low levels of knowledge, understanding, and experience of the Visual Novel game, which is below 50%. Qualitative and quantitative methods combined with structural semiotic approach is used to describe the elements of the design and the signs structure at the Visual Novel. This research can be a scientific reference for further introduce and encourage an understanding of Visual Novel as artwork of Visual Communication Design. In addition, the results may add to the knowledge of society, and encourage the development of Visual Novel artwork that reflect the culture of Indonesia.Visual Novel adalah sejenis permainan audiovisual yang menawarkan kekuatan visual melalui narasi dan karakter visual. Data dari komunitas pengembang Visual Novel (VN) Project Indonesia menunjukkan masih terbatasnya pengembang game lokal yang memproduksi Visual Novel Indonesia. Selain itu, produksi Visual Novel Indonesia juga lebih banyak dipengaruhi oleh gaya anime dan manga dari Jepang. Padahal Visual Novel adalah bagian dari produk industri kreatif yang potensial. Studi ini merumuskan masalah, bagaimana memahami Visual Novel sebagai karya seni desain komunikasi visual, khususnya di kalangan mahasiswa? Penelitian ini merupakan studi kasus yang dilakukan terhadap mahasiswa desain komunikasi visual di lingkungan Universitas Indraprasta PGRI Jakarta. Hasil penelitian menunjukkan masih rendahnya tingkat pengetahuan, pemahaman, dan pengalaman terhadap permainan Visual Novel, yaitu di bawah 50%. Metode kombinasi kualitatif dan kuantitatif dengan pendekatan semiotika struktural digunakan untuk menjabarkan elemen desain dan susunan tanda yang terdapat pada Visual Novel. Penelitian ini dapat menjadi referensi ilmiah untuk lebih mengenalkan dan mendorong pemahaman tentang Visual Novel sebagai karya seni Desain Komunikasi Visual. Selain itu, hasil penelitian dapat menambah pengetahuan masyarakat, dan mendorong pengembangan karya seni Visual Novel yang mencerminkan budaya Indonesia.